Psychometric Standardization of the combinatorial formal operations test of Longeot according to Mokken model - Escurra Mayaute, Luis Miguel (1999)
Psychrometrical properties were evaluated of combining formal operations of Longeot (T.O.F.C.), according to Guttman and Moken model between 260 students of psycholoy faculty of the UNMSM. The result of Guttman’s analysis indicates that an index of reproductiveness is obtained of 0,53. The analysis of items according to Mokken´s model alows to notice that the H(i,j)Loevinger and Delta Star(i,j) coefficients correspond to studied model. The Loevinger’s H coefficientes rises to 0,81, wich one corroborates Longeot’s adjust ment of T.O.F.E. to Mokken’s model the valuation of rho reliability is 0,82. The graphic analysis of curves of items allows to notice that curves are parallel and they don't intersect, verifing the doble monotony that exist between items of T.O.F.C. The instrument smowed having a validity of construction, factorial explorative analysis on the basis of procedure of main components and the Varimax rotation, allowed to smow the existence of only factor. The confiability by internal consistency through Kuder Richardson 20 coefficient, rised to 0,74. The general results indicate that 38,5% of sample correspond to concrete level, the 33,5% to formal a level, and the 28% achieves to Formal B level. The comparisons by sex and promotion indicate that not exist significant differences between the groups.